Effectiveness of Reciproc Blue in removing canal filling material and regaining apical patency. (8th September 2018) - De‐Deus, G.; Belladonna, F. G.; Zuolo, A. S.; Simões‐Carvalho, M.; Santos, C. B.; Oliveira, D. S.; Cavalcante, D. M.; Silva, E. J. N. L.
Abstract: Aim: To compare the efficiency of M‐Wire Reciproc and Reciproc Blue instruments in the removal of root filling material and in their ability to regain apical patency through micro‐computed tomographic (micro‐CT) analysis. Methodology: Ten anatomically matched pairs of teeth, with a single oval‐shaped straight canal, were selected and scanned in a micro‐CT device. The root canals were prepared with M‐Wire Reciproc R25 instruments and filled with gutta‐percha and AH Plus sealer. The root canals were then randomly allocated into two groups ( n  = 10), according to the instrument used: M‐Wire Reciproc and Reciproc Blue. The canals were retreated up to instrument sizes 25 and then 40 in both groups. The surface area and volume of residual filling material were assessed using micro‐CT imaging after the retreatment procedures. The time required to remove the root fillings was recorded. Data were analysed statistically using t ‐test with a significance level of 5%. Results: No significant difference ( P  >   0.05) was observed between the instruments in terms of the volume of residual root filling material. Apical enlargement from size 25 to 40 significantly improved the removal of filling materials ( P  <   0.05). It was possible to regain apical patency in all specimens from both M‐Wire Reciproc and Reciproc Blue groups. No difference was observed in the time required to perform the retreatment between the instruments. Conclusions: Both M‐Wire Reciproc and Reciproc Blue instruments were effective in removing filling materials from oval‐shaped straight canals. Apical patency was reestablished in all specimens.